SASI, KEARIFAN LOKAL DALAM PENGELOLAAN SUMBER DAYA LAUT (Kasus; Masyarakat suku Tanimbar di Desa Adaut, Kecamatan Selaru, Kabupaten Maluku Tenggara Barat) (Jurnal Pelangi : Research of Education and Development, 2013)
The human dependence of nature requires a harmonious relationship between them, in which humans are part of nature itself, which means having to maintain balance and sustainability. In an effort to maintain balance and sustainable marine resources, Tanimbarnise at Adaut village have principles or traditional norms which are respected and practiced in the management of marine products in the form of sasi. SASI enforcement of ocean is primarily intended to keep the sustainability of marine resources that are not disturbed by the exploitation activities carried out continuously, which ultimately makes it the trouble themselves to earn income from marine products. This paper is the result of a research that aims to describe the implementation of marine sasi on Tanimbarnise at Adaut village